Optimal pursuit time in differential game for an infinite system of differential equations - Ibragimov, Gafurjan; Mat Hasim, Risman; Rakhmanov, Askar; Alias, Idham Arif (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
We consider a differential game of one pursuer and one evader. The game is described by an infinite system of first order differential equations. Control functions of the players are subject to coordinate-wise integral constraints. Game is said to be completed if each component of state vector equal to zero at some unspecified time. The pursuer tries to complete the game and the evader pursues the opposite goal. A formula for optimal pursuit time is found and optimal strategies of players are constructed.